The civil service - Trembly, J.E. (My University, 1897)
Introduction: The Civil Service in its general sense, consists of the service rendered by persons whose appointment lies in the power of those officers who are elected by the people. The Civil Service of the United States, previous to the election of Gen. Jackson to the Presidency in 1829 had a career uneventful and very satisfactory to the public. But when Jackson came into power, he introduced his “spoils system” which was adopted by succeeding presidents. This system which has proved such a bane to the government has been carried out, until public sentiment brought about the “merit system”, and attempted to plant purity and honesty in the government service. The “spoils system” still exists to a certain extent, and always will exist in spirit. But the “merit system” now stands supreme, and we hope it may ever stand so. We will see the opposing forces of these two systems as we follow the progress of the Civil Service through its career.
Citation: Trembly, J.E. The civil service. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Political science; Civil service; Theses; Manuscripts (documents)